2018
DOI: 10.1155/2018/1614793
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Anti‐Inflammatory Effects of 80% Methanol Extract of Leonotis ocymifolia (Burm.f.) Iwarsson Leaves in Rodent Models

Abstract: Background Pain and inflammation are the major health problems commonly treated with traditional remedies mainly using medicinal plants. Leonotis ocymifolia is one of such medicinal plants used in folkloric medicine of Ethiopia. However, the plant has not been scientifically evaluated. The aim of this study was to evaluate analgesic and anti-inflammatory effects of the 80% methanol leaves extract of Leonotis ocymifolia using rodent models. Method The central and peripheral analgesic effect of the extract at 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 42 publications
0
29
0
1
Order By: Relevance
“…Plants known to have antimalarial effect have been explored, and many secondary metabolites have been identified [ 39 , 40 ]. In a previous study, the hydroalcoholic extract of the plant was screened for its phytochemical content and shown to have terpenoids, steroids, alkaloids, tannins, flavonoids, and polyphenol compounds [ 41 ]. Several studies have indicated that these metabolites have antiplasmodial activities.…”
Section: Discussionmentioning
confidence: 99%
“…Plants known to have antimalarial effect have been explored, and many secondary metabolites have been identified [ 39 , 40 ]. In a previous study, the hydroalcoholic extract of the plant was screened for its phytochemical content and shown to have terpenoids, steroids, alkaloids, tannins, flavonoids, and polyphenol compounds [ 41 ]. Several studies have indicated that these metabolites have antiplasmodial activities.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation is among the major contributors of pathologic conditions burdening both the developed and the developing nations, especially in the African continent [3]. For instance, chronic inflammation is associated with the emergency and persistence of obesity-associated diabetes mellitus after insulin resistance, among a continuum of other complex human diseases [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, flavonoids, including myricetin and its glycosides, have been shown to possess antioxidant 43 and anti-inflammatory properties due to their ability to inhibit enzymes involved in inflammation, especially the metabolic pathway of arachidonic acid and synthesis of prostaglandins. 44,45 Triterpenic saponins also exhibit antioxidant and anti-inflammatory properties. 46,47 A greater antioxidant and anti-inflammatory activity were observed for the leaf extract, which presented the highest concentration of phenols and flavonoids.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%